Peran Motivasi Intrinsik Dalam Memediasi Hubungan Antara Integritas Dan Profesionalisme Dengan Kinerja Account Representative Kantor Pelayanan Pajak (Kpp) Pratama Semarang Candisari - Nugroho, Andika Yuliana Esti; Indarto, Indarto; Wardoyo, Paulus (PREDIKSI : Jurnal Administrasi dan Kebijakan, 2025)
The aim of this research is to analyze the role of integrity and professionalism on the performance of Account Representatives with intrinsic motivation as an intervening variable at KPP Pratama Semarang Candisari. This research uses quantitative methods using questionnaires to collect the necessary data. The sample in this study was 37, obtained through the census method. The analysis used to process the data uses the Structural Equation Model (SEM) using the Partial Least Square (PLS) approach with the help of the SmartPLS ver. 3.2.9. The results of this research show that integrity has a positive and significant effect on the performance of Account Representatives. Professionalism has a positive and significant effect on the performance of Account Representatives. Intrinsic Motivation has a positive and significant effect on Account Representative performance. Intrinsic Motivation has a positive and significant effect in mediating professionalism on Account Representative performance, but has no effect in mediating the relationship between integrity and Account Representative performance.